Development of Teaching Materials Based on Problem-Based Learning to Improve Critical Thinking Skills: A Systematic Literature Review - Anak Agung Istri Brahmani Prita Dewi; I Wayan Suja; Nyoman Tika; I Wayan Redhana (Jurnal Penelitian Pendidikan IPA, 2025)
Improving critical thinking is an essential 21st-century learning skill, and educational products that nurture it help students advance. Research identifies problem-based learning (PBL) as a highly effective instructional model for fostering critical thinking. This article reviews journal publications from 2019–2025 that explore the development of science teaching materials using the PBL model and their impact on students’ critical thinking abilities. The study aims to provide a comprehensive overview of the types of PBL-based science teaching materials, their effectiveness, and their influence on critical thinking skills. Using the PRISMA literature review method, the researchers conducted identification and screening of abstracts and full texts from 1,200 journal articles, ultimately selecting 12 relevant studies. Analysis of these studies indicates that PBL-based science teaching materials significantly enhance students’ critical thinking, particularly at junior high and high school levels. The findings underscore that integrating PBL into science teaching materials supports inquiry, problem-solving, and analytical reasoning. Consequently, adopting PBL-based resources in classrooms can serve as a strategic approach to strengthen students’ critical thinking processes and better prepare them for complex real-world challenges. This review affirms that PBL-driven science instruction is a powerful tool for 21st-century education.